The Transcription of ZIP9 Is Associated With the Macrophage Polarization and the Pathogenesis of Hepatocellular Carcinoma - Gou, Yingying; Yang, Dan; Tian, Taikun; Zhu, Xingguo; Zhang, Raorao; Ren, Jiaqi; Tu, Dezhen; Luo, Yi; Miao, Yuqing; Zhao, Huan; Wang, Yu; Wei, Bin (Frontiers in Immunology, 2022)
Hepatocellular carcinoma (HCC) is one of the most common digestive system cancers (DSCs) with a poor prognosis. Zinc‐regulated transporter (ZRT)/iron‐regulated transporter (IRT) like protein transporters (ZIPs) encode membrane transport proteins, which are responsible for the absorption of zinc and play important roles in the pathogenesis of various human cancers. Tumor-associated macrophages (TAMs) are important participants in the regulation of tumor microenvironment and the development of HCC. Individual role of each ZIP involved in hepatocarcinogenesis remains elusive. In this study, the transcription patterns of ZIPs in the DSCs were screened firstly through GEPIA2 database. Interestingly, the analysis of the DSCs data showed the distinct mRNA levels of ZIPs between DSCs tissues and healthy controls. Notably, the transcription levels of ZIP2, ZIP5, ZIP8, ZIP9 and ZIP14 were decreased significantly in the tissues of human liver cancer compared to paracarcinoma liver tissues. To further confirm the mRNA transcriptional changes of Zips in HCC, N-Nitrosodiethylamine (DEN) combined with carbon tetrachloride (CCl4) inducing mouse model of HCC were established. Consistently, the mRNA levels of Zip2, Zip9， and Zip14 in liver tissues of HCC induced mice were also decreased compared with the healthy controls. In addition, mouse peritoneal elucidated macrophages (PEMs)-derived M1/M2 macrophages in vitro, as well as human patients of HCC-derived TAMs, were used to examine the transcription levels of ZIPs. Our results showed that both Zip2 and Zip9 were up-regulated in M2-polarized macrophages. Zip2 transcript was also up-regulated M1-polarized macrophages, but Zip9 was slightly down-regulated. TAMs generated from human liver cancer tissues also displayed a decrease in ZIP9 transcription compared to paracarcinoma tissues. To further explore the role of Zip9 in M1/M2 polarization, the siRNA knockdown results revealed that Zip9, but not Zip2, could promote M2 macrophage polarization and impair M1 macrophage polarization. Mechanistically, Zip9 enhances phosphorylated STAT6 to promote M2 macrophage polarization but suppresses the phosphorylation of IκBα/β to inhibit M1 macrophage polarization. Together, our results indicate that ZIP9 may involve in macrophages polarity in HCC development and may be a potent new biomarker for the diagnosis of HCC.